2019
DOI: 10.31557/apjcp.2019.20.2.417
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Colposcopic Biopsy Results of Patients Who have Cytomorphological Normal but HPV 16-18 or Other High-Risk HPV Subtypes Positive

Abstract: Objective:Current guidelines suggest annual co-test follow-up in non-16/18 high-risk HPV positive patients without abnormal cytologic findings. Considering the relatively high false-negative rates of cervical cytology, a follow-up period of one year might constitute an additional risk for development of cervical malignancies in these patients. The current study aims to evaluate colposcopic biopsy results of cytologically normal patients detected to carry high risk HPV by screening tests. Materials and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 11 publications
2
16
2
Order By: Relevance
“…In our study, 12.18% of the HPV16 infected and 12.15% of the HPV18 positive women suffered from HSIL or SCC, followed by HPV51 (9.88%), HPV56 (8.82%), HPV66 (8.33%), and HPV52 (7.94%). HPV16 and 18 showed strong pathogenicity, which was consistent with previous literature reports 25,26 . We noted that 14.29% HPV73 positive women were diagnosed with HSIL.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, 12.18% of the HPV16 infected and 12.15% of the HPV18 positive women suffered from HSIL or SCC, followed by HPV51 (9.88%), HPV56 (8.82%), HPV66 (8.33%), and HPV52 (7.94%). HPV16 and 18 showed strong pathogenicity, which was consistent with previous literature reports 25,26 . We noted that 14.29% HPV73 positive women were diagnosed with HSIL.…”
Section: Discussionsupporting
confidence: 92%
“…In LSIL cases, non‐16/18 single and multiple HPV infections accounted for 66.78%, implying a higher risk of disease than HPV16/18. Therefore, the pathogenic risk of non‐16/18 HPV infection in samples from this region was significantly higher than the United States and European countries 26,27 . The top four most frequently infected HPV in HSIL (or SCC) patients were HPV16, HPV52, HPV18, HPV58.…”
Section: Discussionmentioning
confidence: 88%
“…We found that the rate of CIN 2+ lesion was 18.6% in women with negative cytology. A study investigating cervical biopsy results in women with cytomorphological normal but HPV 16/18 positive reported that the rate of ≥HSIL lesions was 48.2% 19 . Han et al 20 found that one (1.6%) of 64 HPV‐infected patients with negative cytology had adenocarcinoma, two (3.1%) patients had adenocarcinoma in situ, and three (4.7%) patients had CIN 2/3.…”
Section: Discussionmentioning
confidence: 99%
“…Aydoğmuş and Aydoğmuş (9) reported that the ratio of CIN 2+ lesions in cases of normal cytology results with non-16/18 HPV subtypes was 15.6%. Conversely, in another research, this ratio was reported as 0.01% (10).…”
Section: Discussionmentioning
confidence: 99%